Criticism of philosophical translation: the case of Jacques J. Derrida - Castro Ramírez, Nayelli (Íkala, Revista de Lenguaje y Cultura, 2008)
This article discusses philosophical translation criticism based on the Derridian texts. Firstly, I review some of the critiques made by J. Derrida on the French translation of Plato’s Phaedrus. Some of the problems raised there allow me to demonstrate the polysemous textual fabric of philosophy and define the notion of deconstructive criticism. The second part presents some of the characteristics of philosophical translation from terminology’s point of view and analyzes the Spanish and French retranslations of the Hegelian concept Aufhebung. Finally, in the third part I attempt to show that Derridian texts require a sort of criticism borrowing both from A. Berman’s and H. Meschonnic’s translation criticism projects. Received: 26-11-2007 / Accepted: 08-07-2008 How to reference this article: Castro Ramirez, N. (2008). La crítica de traducción filosófica: el caso de Jacques J. Derrida. Íkala. 13(2), pp.15-28.